PRODUKSI BIOETANOL DARI SINGKONG (Manihot utilissima) DENGAN SKALA LABORATORIUM - Jhiro Christian Mailool; Robert . Molenaar; Dedie . Tooy; Ireine A. Longdong (Universitas Sam Ratulangi, 2013)
ABSTRACTThis research aims to study techniques bioethanol production from cassava to produce ethanol from cassava and determines the quality of the bioethanol produced by analyzing the ethanol content and pH as well as knowing the yield of bioethanol produced from the process is used. The results have been known to a variety of constraints in the production process from raw material storage, fermentation and distillation that can affect the end result in obtaining bioethanol from cassava. By using 5 kg of cassava feedstock with 3 times distillation process which has produced 215 ml of ethanol to 53% ethanol content and pH 6.902; 185 ml of ethanol to 74% ethanol content and pH 6.927, and 130 ml ethanol with 49% ethanol content and pH 6.573.Keywords: Bioethanol.